Phytoremediation potential of Equisetum hyemale in diverse waste management: A decade-long literature synthesis on water Bamboo’s role in industrial and domestic effluent treatment - Faizsyahrani, Lilla Panca; Ulfah, Maria; Sumarno, Sumarno; Hayat, Muhammad Syaipul (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2023)
Escalating waste production due to population growth and diverse community activities poses environmental and public health threats. To mitigate these effects, this study investigates using water bamboo (Equisetum hyemale) in phytoremediation. A comprehensive literature review was conducted, analyzing articles from 2011-2024 from Indonesian language journals. Ten articles were selected, focusing on the phytoremediation of four types of waste: tofu industry waste, leachate, domestic waste, and lead. Findings reveal water bamboo’s potential as a phytoremediation agent, effectively reducing waste levels in various contexts. For instance, it reduced BOD, COD, and TTS in tofu industry waste; Pb, Zn, Cr, DO, and pH in leachate waste; BOD, COD, and detergent levels in domestic waste; and lead in lead (Pb) industrial waste. The study underscores the potential of water bamboo in real-world liquid waste management applications, contributing to sustainable waste management strategies and addressing environmental and public health challenges.